Manajemen Pembelajaran Ilmu Tajwid Melalui Nadhom Di Pesantren - Islami, Azmi; Imroatun, Imroatun; Nurlaeli, Nurlaeli; Sajid, Dind Ibra Benign; Samael, Parid; Arifin, Zainul (Universitas Cokroaminoto Yogyakarta, 2024)
This research demonstrates how adult female students at the Pondok Pesantren Riyadul Awamil Islamic, Serang Regency, understand Ilm Tajwid utilizing nadhom in the book Tuhfatul Atfal Wal Ghilman Fi Tajwid al-Quran (Tuhfatul). This kitab kuning is used at Islamic boarding schools throughout Indonesia, even Southeast Asia as a manual for reading the Quran. In order to gather information for this qualitative case study, interviews with Kyai, ustazah, and a select group of students were conducted along with observations of how the learning was being put into practice. this education was inextricably linked to the standard pesantren curriculum for mastering the kitab kuning. Its power comes in the ease with which students can learn the contents of the Tuhfatul book because the nadhoms are regular and rhythmic lines that students can easily pronounce, sing, and remember. Spreading its use to the community may be offered, along with suggestions for adjusting the learning process to the learner.